Design and Fabrication of Composite Monocoque Chassis for Formula Student Racing Car - Alief Wikarta; Ismail Maydiyanto (JMES: The International Journal of Mechanical Engineering and Sciences, 2023)
This study uses a combination of analytical, simulation, and experimental methods in the design process of a sandwich-structured composite monocoque chassis. The analytical method, which determines the stiffness value of the composite, depends on the number of layers and the orientation of the fiber angle. The simulation method, which is based on the finite-element method, is used to validate the stiffness value. The experimental method involves a 3-point bending test used to verify the effectiveness of the design produced by analytical and simulation methods. After all model designs were validated through simulation and experimental methods, the next stage is fabrication. The stiffness and strength are achieved with variations, which have combined layup orientation angles of 0° and 45°. This can be applied to all panels, regardless of the number of layers. Based on the design results, the processes involved in fabricating the monocoque chassis begin with the manufacture of molds and the lay-up of carbon fiber. The process is continued by inserting the prototype into the oven, after which the final product then undergoes finishing to prepare it for use. The fabricated monocoque chassis has been used in 2 events in Japan’s annual Formula SAE student racing car competition.